Painting panel on the beams of the Mandapa - Temples of India Project Team (Jio Institute, 2024)
This is a painting panel on the beams of the mandapa (pillared hall) of the Bhandasar Temple. It is a set of five paintings drawn with the purpose of telling people that what are the wrongdoings that should be avoided. In every painting, a demonic figure is shown punishing the person who has violated moral laws. The five paintings have inscriptions of the acts that Jainism condemns. These are, ‘Kamchesta ka phal, Manushya ko maarne ka phal, chor ko saahaj dene ka phal, Biswas ghat ka phal’ (punishments for indulging in wrong sexual activities, killing a human being, supporting a thief and betrayal).